Cumacea from Jørgen Brønlund Fjord, North Greenland. - Just, Jean (Meddelelser om Grønland, 1970)
From Jørgen Brønlund Fjord, North Greenland (82°10’ N, 30°30’ W) 11 species of Cumacea are listed as the result of investigations during the Fourth Peary Land Expedition in the summer of 1966. One species is new to science, viz. Campylaspis stephenseni. The male of Leucon spinulosus H . J . HANSEN is recorded and described for the first time. A possibly new species of the genus Eudorella is described, but in view of recent papers it is referred to as Eudorella sp. only. Notes on breeding biology are made where possible.